Enhanced thermoelectric properties of nano SiC dispersed Bi2Sr2Co2Oy Ceramics. (20th April 2018) - Hu, Qiujun; Wang, Kunlun; Zhang, Yingjiu; Li, Xinjian; Song, Hongzhang
Abstract: The thermoelectric properties of Bi2 Sr2 Co2 Oy + x wt% nano SiC (x = 0.00, 0.025, 0.05, 0.1, 0.2, and 0.3) prepared by the solid-state reaction method were investigated from 300 K to 923 K. The resistivity can be reduced effectively by adding a small amount of SiC nano particles, which is attributed to the increase of the carrier concentration. At the same time, the Seebeck coefficients can be improved effectively due to the energy filtering effect that low energy carriers are strongly dispersed at the interface between the SiC nano particles and the matrix. The decrease of thermal conductivity is due to the increase of the scattering ability of the phonons by the SiC nanoparticles distributed at the boundary of the matrix. As a result, the Bi2 Sr2 Co2 Oy + x wt% SiC composites exhibit better thermoelectric properties. The maximum ZT value 0.24 is obtained when x = 0.05 at 923 K. Compared with the sample without SiC nano particles, the ZT value is increased by about 59.7%.